Thinking about the environment and theorising change: how could Life History Strategy Theory inform mHealth interventions in low- and middle-income countries? - Barak Morgan; Xanthe Hunt; Mark Tomlinson (Global Health Action, 2017)
Background: There is a growing body of literature outlining the promise of mobile information and communication technologies to improve healthcare in resource-constrained contexts. Methods: We reviewed the literature related to mobile information and communication technologies which aim to improve healthcare in resource-constrained contexts, in order to glean general observations regarding the state of mHealth in high-income countries (HIC) and low- and middle-income countries (LMIC). Results: mHealth interventions in LMIC often differ substantively from those in HIC, with the former being simpler, delivered through a single digital component (an SMS as opposed to a mobile phone application, or ‘app’), and, as a result, targeting only one of the many factors which impact on the activation (or deactivation) of the target behaviour. Almost as a rule, LMIC mHealth interventions lack an explicit theory of change. Conclusion: We highlight the necessity, when designing mHealth interventions, of having a theory of change that encompasses multiple salient perspectives pertaining to human behaviour. To address this need, we explore whether the concept of Life History Strategy could provide the mHealth field with a useful theory of change. Life History Strategy Theory may be particularly useful in understanding some of the problems, paradoxes, and limitations of mHealth interventions found in LMIC. Specifically, this theory illuminates questions regarding ‘light-weight’ programmes which solely provide information, reminders, and other virtual ‘nudges’ that may have limited impact on behaviours governed by extrinsic structural factors.